2007
DOI: 10.1021/bm070349f
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Structural Imperfection on Gelatinization Characteristics of Amylopectin Starches with A- and B-Type Crystallinity

Abstract: The aim of the present work was to investigate the effect of physical structures on the properties of starch granules. Starches with a high amylopectin content possessing A- and B-type crystallinity were chosen for the study. The gelatinization temperature decreased in the following order: maize (A) > potato (B) > wheat (A) > barley (A), which did not reflect a correlation with the type of crystallinity. Low values of gelatinization temperature were accompanied with high free surface energy of the crystallites… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
49
1
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 91 publications
(57 citation statements)
references
References 41 publications
(104 reference statements)
5
49
1
2
Order By: Relevance
“…Thus, apparently the A fp -chains remained in the cluster preparation and further down to the isolated building blocks, which contradicts our earlier suggestion that these chains are not part of the actual clusters because of their short lengths that make them unsuitable for double helix formation [7,8]. As actual part of the clusters, they might therefore introduce defects into the double helix organisation in the crystalline lamellae thereby affecting starch granule properties [39][40][41][42].…”
Section: Chain Composition In Building Blocks and Clusterscontrasting
confidence: 59%
“…Thus, apparently the A fp -chains remained in the cluster preparation and further down to the isolated building blocks, which contradicts our earlier suggestion that these chains are not part of the actual clusters because of their short lengths that make them unsuitable for double helix formation [7,8]. As actual part of the clusters, they might therefore introduce defects into the double helix organisation in the crystalline lamellae thereby affecting starch granule properties [39][40][41][42].…”
Section: Chain Composition In Building Blocks and Clusterscontrasting
confidence: 59%
“…Blue circles symbolize A-chains, red circles external B-chains, gray circles are glucose residues involved in a branch linkage (arrows), and yellow circles are residues in internal segments of B-chains. Note that the chain segment that carries the reducing end (/) is regarded as an internal segment Bertoft et al (2008) c Kalinga et al (2013) d Hanashiro et al (2002) e Zhu et al (2011a) ECL corresponds rather well to the reported thickness of the crystalline lamellae in starch granules (Table 1.1) (Kiseleva et al 2005;Genkina et al 2007;Koroteeva et al 2007a;Kozlov et al 2007a).…”
Section: Major Chain Categoriessupporting
confidence: 66%
“…The strands of the double helix are left handed and consist of six glucose residues per turn and a pitch of 2.1 nm. The length of the double helices corresponds approximately to the experimentally estimated thickness of the crystalline lamellae, i.e., 4.0-6.5 nm, depending on the type of starch (Table 1.1) (Kiseleva et al 2005;Genkina et al 2007;Koroteeva et al 2007a;Kozlov et al 2007a). …”
Section: Lamellar Structurementioning
confidence: 79%
See 1 more Smart Citation
“…5 and Table 2) along with a narrowing of the endothermic peak as demonstrated by the T f -T o values (GENKINA et al, 2007). The increase in stability of the crystalline zones must have required higher temperature to melt the crystallites.…”
Section: Thermal Propertiesmentioning
confidence: 91%